2013
DOI: 10.5539/gjhs.v6n1p135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sphenoid Sinuses for Sudanese Population Using Computed Tomography

Abstract: The purpose of this study is to determine the anatomical features of the sphenoid sinus using computerized tomography (CT).100 Sudanese subjects were investigated for CT sinuses; Characterization of the sphenoid sinus and seven horizontal and vertical measurements were evaluated.Onodi cell was found in 13 subjects, 10 of them were sellar and 3 were pre-sellar. Pneumatization was of the sellar type in 85%, presellar was 15%, and no subject was chonchal.The mean length of vertical lines from the center of spheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
4
10
1
Order By: Relevance
“…Type of pneumatization: The three types to Hammer and Radberg (1961) [15] have been found. The sellary type (62%) predominated in agreement with the literature [4,7,8,9,18]. On the other hand, the proportions were lower than those of most studies [15,18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Type of pneumatization: The three types to Hammer and Radberg (1961) [15] have been found. The sellary type (62%) predominated in agreement with the literature [4,7,8,9,18]. On the other hand, the proportions were lower than those of most studies [15,18].…”
Section: Discussionsupporting
confidence: 90%
“…The sellary type (62%) predominated in agreement with the literature [4,7,8,9,18]. On the other hand, the proportions were lower than those of most studies [15,18]. The sellar type predominated in men (50 out of 80 cases) [18] while the presellary type predominated in women (12 out of 20 cases).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sphenoid sinuses are surrounded by vital neurovascular structures, such as the internal carotid artery, opticnerves, maxillary and vidian nerves. The description of these anatomic variants in different populations gives useful information [6] [7] [8]. A previous work has studied the anatomic variants of sphenoidal sinuses and adjacent structures amongst Beninese [9].…”
Section: Introductionmentioning
confidence: 99%
“…In line with our results, Barghouth et al 7 , Degirmenci et al 8 , Ariji et al 14 , and Koppe et al 15 found that the MS volume did not show dimorphism. Kajoak et al 16 performed linear measurements on CT images of SSs in a Sudanese population and reported that the studied parameters showed significant differences not only between genders but also from other populations. Other studies, in line with our findings, have reported significantly greater SS volumes in males.…”
Section: Discussionmentioning
confidence: 99%